A Novel Model Predictive Current Control for Asymmetrical Six-Phase PMSM Drives With an Optimum Duty-Cycle Calculation Scheme - Jin Zhang; Feng Yu (IEEE Access, 2023)
This paper presents a novel model predictive current control (MPCC) with an optimum duty-cycle calculation scheme for asymmetrical six-phase permanent magnet synchronous machine (ASPMSM) drives. The proposed method takes advantages of the steady-state performance improvement and the weighting factor elimination. Both merits are owing to the optimum duty-cycle calculation scheme. On the one hand, for the $α $ - $β $ subspace, the optimal voltage vector set (VVS) is chosen from twelve ones and the corresponding optimal duty cycles are calculated using the proposed scheme. On the other hand, for the x-y subspace, the VVS can be determined according to that of $α $ - $β $ subspace and the optimal duty cycles are deduced using the same scheme. The voltage vector references in two subspaces are then obtained, and they are transformed to six-phase voltages for controlling the six-phase inverter. The proposed method is verified by experimental results based on a 2 kW ASPMSM prototype.